ทัศนคติของครัวเรือนในเขตเทศบาลนครพระนครศรีอยุธยา ต่อการจัดการขยะแบบ 3Rs / Household's Attitude toward Waste Management by 3Rs Approach in Pra Nakorn Sri Ayutthaya Municipality - พุ่มภิญโญ / Sauwaluck Koojaroenprasit and Sumaree Pumpinyo, เสาวลักษณ์ กู้เจริญประสิทธิ์ และสุมาลี (Journal of Community Development Research (Humanities and Social Sciences), 2017)
การศึกษาครั้งนี้มีวัตถุประสงค์ เพื่อศึกษาทัศนคติของครัวเรือนในเขตเทศบาลนครพระนครศรีอยุธยาต่อการจัดการขยะแบบ 3Rs โดยการเก็บแบบสอบถามจากกลุ่มตัวอย่าง จำนวน 400 ครัวเรือน โดยใช้การวิเคราะห์ผลด้วยวิธีวิเคราะห์ข้อมูลเชิงคุณภาพและวิธีวิเคราะห์ข้อมูลเชิงสถิติ      ผลการสำรวจ ทัศนคติของครัวเรือนต่อการจัดการขยะตามแนวคิด 3Rs พบว่า ครัวเรือนมีความรู้ความเข้าใจเกี่ยวกับแนวคิด 3Rs อยู่บ้างแล้ว เนื่องจากเทศบาลฯ ร่วมกับหน่วยงานที่เกี่ยวข้อง เคยจัดกิจกรรมส่งเสริมการจัดการขยะตั้งแต่ต้นทางมาหลายครั้ง ครัวเรือนเห็นด้วยกับประเด็นต่างๆ ดังนี้ 1. การจัดการขยะตามแนวคิด 3Rs ให้เกิดผลนั้น เป็นเรื่องของทุกส่วนในสังคมที่ต้องร่วมมือกัน 2. การคัดแยกขยะช่วยให้ปริมาณขยะในภาพรวมลดลง 3. การแยกขยะทำให้สามารถนำขยะไปใช้ประโยชน์ได้มากขึ้น 4. แนวคิด 3Rs เป็นพื้นฐานของการจัดการขยะแบบยั่งยืน 5. ขยะเป็นปัญหาใหญ่ที่ต้องเร่งแก้ไข 6. การแยกขยะจะเกิดผล หากมีแรงจูงใจและมีกฎหมายควบคุม      ทัศนคติต่อแนวคิดการจัดการขยะแบบ 3Rs โดยรวมจำแนกตามอาชีพ ผลการศึกษา พบว่า กลุ่มอาชีพข้าราชการ พนักงานบริษัท รัฐวิสาหกิจมีทัศคติที่ดีที่สุดต่อแนวคิดการจัดการขยะแบบ 3Rs      ข้อเสนอแนะจากการศึกษา คือ ควรส่งเสริมการคัดแยกและการใช้ประโยชน์จากขยะตั้งแต่ระดับครัวเรือน การสร้างสังคมรีไซเคิลโดยจัดกิจกรรมให้องค์กรท้องถิ่นมีส่วนร่วมในการจัดการขยะตั้งแต่ต้นทาง      The objective of this study is to study the attitude of the local households in Phra Nakorn Sri Ayudhaya Municipality on 3Rs concept for waste management. Data collection was done by the questionnaire survey to 400 households. Data analysis applied a qualitative research technique and a statistical analysis approach.      The results of people’s attitude showed that they were aware of 3Rs concept since the municipality, together with its partnership, implemented the promotional programs of waste management at sources to the local communities. Household agreed that 1. Waste management by 3Rs concept should be the participation of all relevant stakeholders; 2. Waste separation will reduce the amount of waste; 3. Waste separation will make waste more useful; 4. 3Rs concept is the basic for sustainable waste management; 5. Waste is the critical issue; 6. Waste separation will be successful because of the incentives and enforcement by laws.      As for their occupation types, the results showed that government officers, company officers and state enterprise officers have the best attitude toward 3Rs waste management concept.      The recommendation for this study are: to encourage local households for waste separation and utilization at sources; and to create recycling society of waste management at source by enhancing participation of all relevant stakeholders.
Keywords: ทัศนคติ การจัดการขยะ 3Rs; Attitude, Waste Management, 3Rs